Mapping SMEs financial literacy research: bibliometric analysis and literature review - Molina-García, Antonio; Campos-Valenzuela, Marta; Galache-Laza, María Teresa; Diéguez-Soto, Julio (My University, 2021)
Financial literacy in SMEs constitutes an emerging research field, increasing its scientific production exponentially in recent years, and in a very heterogeneous way. The purpose of this paper its to review 88 contributions for the period 2005-2020 through bibliometric techniques. Specifically, we carry out a co-occurrence and co-citation analysis of the keywords and cited references to obtain two thematic clusters and four theoretical roots. Thus, through its combination in five thematic groups, we develop an integrative framework that allow us to identify the research paths addressed, and propose important lines of future research, providing a research guide for scholars.
Keywords: Bibliometría; Financial literacy; SMEs; Bibliometric analysis; Literature review; Co-occurrence analysis; Co-citation analysis